Aspectos da Heterogeneidade nas Agriculturas Familiares da Microrregião de Toledo/PR e do Território Norte Pioneiro Paranaense - Dimas Soares Junior (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
The heterogeneity of production structure and models is striking in Brazilian agriculture. The concept of “family agriculture” defined in law conceals a great diversity present also in this stratum of production.The 2006 agricultural census with the definition of Pronaf criteria for classification of this public offers the possibility to identify and discuss the distinctions present between the different types of family farmers. This article purpose assess, characterize and analyze comparatively the presence of such distinctions in the Paraná state and in two of its regions, with different occupation histories and contrasting development indexes. For this, the census datas were grouped with information about farmers, farms, economic activities, income and occupation. It was observed that Pronaf correspond to about 75% of the total farms in Paraná and in the two regions studied, with a predominance of group B in the state and in the Northern Pioneiro and group C in the Toledo region. The most relevant differences observed between regions and between types of farmers are found in variables such as the degree of associativism and the availability or not of agricultural advisory. As a similarity observed, we highlight the remarkable presence of the farmers of the Pronaf group B in the older age classes, reinforcing the concern with the succession processes in family agriculture.